Histological Effects of Copper-treated Water Media on the Kidney of Oreochromis niloticus fingerlings - Tobias, Ermelinda; Carino, Virginia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Sublethal concentrations of copper as copper sulphate (CuSO4, 5H2O) were used to treat the water media where Oreochromis niloticus fingerlings were reared. Samples of fingerlings were taken after 15, 30 and 45 days of exposure for light microscope studies. In both concentrations used, dense bodies, interstitial damage, vacuolations, casts in the lumina, tubular necrosis and other degenerative changes were observed in varying degrees and frequency of occurences.